Estrategias de aprendizaje del idioma kichwa para la competencia comunicativa, en el quinto grado de Educación General Básica de la Unidad Educativa Adolfo Kolping, del cantón Riobamba, en el año lectivo 2022-2023. - Morocho Pichazaca, Maria Doralisa (2023)
This research aims to design learning strategies for the Kichwa language for the communicative competence of the students of Secondary Basic Education of the "Adolfo Kolping" Educational Unit. This study was supported by reliable information and the researcher's contribution to the educational and social reality. The research methodology was based on a qualitative approach because subjectivity intervened through the qualitative survey, observation, and interview techniques, using instruments such as the questionnaire, the observation sheet, and the list of questions.With the information gathered, we proceeded to interpret the data and found that adequate learning strategies related to the ommunicative competence of the Kichwa language had yet to be applied. According to the results obtained, it was evidenced that the communicative competence of the Kichwa language needs to be developed in its totality. There are gaps and difficulties in the learning process due to several circumstances; among them are the teaching performance based on Spanish as the fundamental language for communication during the development of the class and the lack of strategies that promote the communicative approach. This limits the learning process in the students, who are continuously motivated. Therefore, it is necessary for the teacher's intervention in the classroom through the application of playful activities based on linguistic skills, such as speaking, listening, reading, and writing, to construct meaningful and practical learning in daily life. Finally, it is concluded that developing strategies to promote communication and, therefore, learning experientially is essential.